Antiviral Properties and Potential of Ginger (Zingiber Officinale) and Its Derivatives: A Systematic Review - Nouman Ahmad; Hamdan Ahmad; Dewi Syarifah; Vivian Soetikno (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
Antiviral Properties and Potential of Ginger (Zingiber Officinale) and Its Derivatives: A Systematic Review. Ginger has long been valued in traditional medicine for its therapeutic benefits. Recently, its antiviral capabilities have attracted significant interest, highlighting its potential as a natural antiviral agent. This systematic review seeks to thoroughly evaluate the antiviral effects of ginger and its active compounds, providing valuable insights to support future research and clinical applications in natural antiviral therapies. A comprehensive electronic search was undertaken across PubMed, Embase, and Scopus databases, employing MeSH terms, Emtree, and relevant synonyms to capture studies on ginger and its antiviral effects. The initial search yielded 531 records, which were de-duplicated and subsequently screened by title and abstract using Rayyan software. Fourteen studies specifically addressing antiviral effects against human pathogens met the inclusion criteria. This systematic review was conducted in strict accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure rigorous reporting of findings. The majority of included studies were in vitro, revealing anti-viral effects of ginger against various viruses, including Influenza A, Chikungunya, Dengue, hRSV, HSV-2, and SARS-CoV-2 in different cell lines across various concentrations. In addition, Ginger extracts also demonstrated efficacy against Influenza A in both in vivo and in ovo studies, and a randomized controlled trial showcased encouraging antiviral effects targeting SARS-CoV-2. Ginger shows promising antiviral effects in most of the in vitro studies. Translating these findings to in vivo models is imperative for clinical relevance. Further in vivo research is essential before progressing to human studies to ascertain ginger's potential as an effective antiviral agent